2016
DOI: 10.1016/j.ijpharm.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of process parameters on the preparation of pharmaceutical films by electrostatic powder deposition

Abstract: Electrostatic powder deposition (ESPD) has been developed as a solvent-free method to prepare pharmaceutical films. The aim of this work was to investigate the influence of process parameters during (1) electrostatic powder deposition, (2) curing, and (3) removal of the film from the substrate on the properties of the film. Polyethylene oxide (PEO) was used as the model polymer and stainless steel 316 as the substrate. Deposition efficiency (i.e. deposited weight) was measured with varying charging voltage, gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Disintegration time of each film formulation was determined using Petri dish method [3]. A film strip of 2 x 2 cm² dimension was placed in a petri dish containing 25 mL of phosphate buffer, pH 6.8 at 37 °C and stirred.…”
Section: Disintegration Timementioning
confidence: 99%
See 1 more Smart Citation
“…Disintegration time of each film formulation was determined using Petri dish method [3]. A film strip of 2 x 2 cm² dimension was placed in a petri dish containing 25 mL of phosphate buffer, pH 6.8 at 37 °C and stirred.…”
Section: Disintegration Timementioning
confidence: 99%
“…However, in conditions like motion sickness the patient requires prompt treatment [2]. Orally disintegrating films (ODFs) of APIs have gained attention as an alternate dosage form in such cases [3]. ODFs are the thin oral strips consisting of polymeric base material, drug and other excipients [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the powder particles under electrostatic coating are more dispersed and deposited on the target when compared to nonelectrostatic coating. Several authors also found better transfer efficiency when applying electrostatic coating of seasonings on food targets [7,[11][12][13][14] .…”
Section: Transfer Efficiencymentioning
confidence: 97%
“…Coating evenness shows how well food powder is dispersed on the target; therefore, it directly affects the appearance of food product and consumer acceptability [6] . High powder adhesion is also expected in the electrostatic coating because of the better attraction force of charged particles of powder on the surface of food target [7] . During processing, dust, powder build-up and overuse of food powders can be minimized by using electrostatic coating, therefore; the worker health issues and cleaning process can be reduced, resulting in lower operating costs [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…After deposition, the powder has to remain in place long enough to enable film formation by heat-induced coalescence of the individual particles. A smooth and homogeneously thick coating is achieved by reduction of the free volume, while its hardening takes place on cooling [89]. Any powder able to accumulate charge with a low decay rate is potentially suitable for being employed as an electrostatic dry coating agent [90].…”
Section: Electrostatic Coatingmentioning
confidence: 99%